2011
DOI: 10.1118/1.3586038
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of electron and isotopes dose point kernels with fluka Monte Carlo code for dosimetry in nuclear medicine therapy

Abstract: FLUKA provides reliable results when transporting electrons in the low energy range, proving to be an adequate tool for nuclear medicine dosimetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
84
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 41 publications
11
84
0
2
Order By: Relevance
“…With the same number of simulated particles, the accordance between FLUKA and 3D-RD or MCID (table 3) is slightly worse than that between FLUKA and VKC (table 2), probably due to the small differences between the simulation algorithms used by the three codes (FLUKA, EGSnrc, MCNP5) in homogeneous water. In fact, the differences in table 3 are similar to those commonly observed when comparing different simulation algorithms (Botta et al 2011, Uusijarvi et al 2009). When comparing FLUKA DMC and VKC, instead, no differences regarding the simulation algorithm come into play since the voxel kernels for VKC were calculated with FLUKA and with the same simulation parameters as for the DMC simulation.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…With the same number of simulated particles, the accordance between FLUKA and 3D-RD or MCID (table 3) is slightly worse than that between FLUKA and VKC (table 2), probably due to the small differences between the simulation algorithms used by the three codes (FLUKA, EGSnrc, MCNP5) in homogeneous water. In fact, the differences in table 3 are similar to those commonly observed when comparing different simulation algorithms (Botta et al 2011, Uusijarvi et al 2009). When comparing FLUKA DMC and VKC, instead, no differences regarding the simulation algorithm come into play since the voxel kernels for VKC were calculated with FLUKA and with the same simulation parameters as for the DMC simulation.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, FLUKA dose point kernels were calculated in water and bone tissue for both monoenergetic electrons and beta emitting isotopes, and compared to those obtained with other MC codes commonly used for nuclear medicine dosimetry (Botta et al 2011). This latest study showed that the differences between the simulation algorithms of the different codes are not expected to have an impact when performing internal dosimetry at the voxel level.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond 10 mm, the dose contribution is nil. X 90 was evaluated from the concentric shells simulation to be 0.533 cm, which compares well with 5.34 mm reported by Simpkin [24] and 5.4 mm reported by Botta [25]. Consequently, this comparison appears to justify the use of simulated kernels in the dose convolution calculations (Figures 4 and 5).…”
Section: Y-90 Dose Point and Dvksupporting
confidence: 77%
“…In this regard, it is crucial to use a Monte Carlo code that provides an event-by-event simulation, as a loss of spatial resolution during particle transport from condensed simulation algorithms (i.e., grouping elastic, inelastic, and radiative events), and underestimation of secondary electrons, have a large effect on energy deposition (23). PENELOPE can perform event-by-event coupled photon-electron transport simulations, thus providing a more accurate estimation of the energy deposition than is possible with other general-purpose Monte Carlo codes (24,25).…”
Section: Discussionmentioning
confidence: 99%